EXPLORING THE EFFECTIVENESS OF USING TIK TOK AS A MEDIA FOR PROMOTION: A CASE STUDY OF YOUTH INTENTION TO BUY PRODUCTS - Pieter, Gabriela M.; Massie, James D.D.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The more creative a promotional activity, the stronger the marketing appeal to consumer purchase intentions. Moreover, using technological advances in marketing activities. Therefore, many business people use various ways to compete in the market, one of which is using social media applications in product promotion activities so that these products can be quickly recognized by many people. One form of marketing activity that can quickly disseminate information about a product and the introduction of a product's brand is social media marketing. This research aims to explore the effectiveness of using TIK TOK as a media for promotion (A case study of youth intention to buy products). Researchers conducted this research through qualitative methods. The sampling technique that will be used is purposive sampling. Knowing that the population is huge in number, therefore, for this research, the researcher took only 15 representative respondents of each field. The respondents or informants of this research are the youth users of the TIK TOK application, who are interested in the marketing content from this app, which is the promoting product's content using this application. This research had two variables in order to explore the effectiveness of using TIK TOK as a media for promotion: a case study for youth intention to buy products, which is social media marketing on TIK TOK and Intention to buy products. The result after conducting the interview, almost all of them are viewers, but some of them are also viewers and content creators but they are not that intense in creating content. Many of them like product promotional content such as skincare and outfits, but some of them also like other promotional content such as electronic products, food promotions, unique stuff, and also products for motorbikes.Â Keywords: social media marketing, intention to buy, promotional content, Tik Tok, youth.